2012
DOI: 10.1002/adma.201202789
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Mobility Increase and Threshold Voltage Reduction in Organic Field‐Effect Transistors by Overlaying Discontinuous Nano‐Patches of Charge‐Transfer Doping Layer on Top of Semiconducting Film

Abstract: An effective strategy for significantly increasing the organic transistor mobility with simultaneous reduction of the threshold voltage utilizing discontinuous nano-patches of charge-transfer doping layer is demonstrated. By overlaying the nano-patches on top of a given semiconducting film, mobility and threshold voltage of p-type pentacene are remarkably improved to 4.52 cm(2) V(-1) s(-1) and -0.4 V, and those of n-type Hex-4-TFPTA are also improved to 2.57 cm(2) V(-1) s(-1) and 4.1 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…Notably, trap filling may be advantageous for OTFT applications where a conductive film is not desired and where trap filling by a dopant has been shown to enhance mobilities and permit control over the threshold voltage. 3134 This attribute of DMBI dopants was exploited in another work, where it was found that TIPS-pentacene can be doped with o -MeO-DMBI to obtain high-mobility n-channel transistors without increasing the bulk conductivity, as is commonly observed when doping organic transistors. 35 …”
Section: Discussionmentioning
confidence: 96%
“…Notably, trap filling may be advantageous for OTFT applications where a conductive film is not desired and where trap filling by a dopant has been shown to enhance mobilities and permit control over the threshold voltage. 3134 This attribute of DMBI dopants was exploited in another work, where it was found that TIPS-pentacene can be doped with o -MeO-DMBI to obtain high-mobility n-channel transistors without increasing the bulk conductivity, as is commonly observed when doping organic transistors. 35 …”
Section: Discussionmentioning
confidence: 96%
“…Discontinuous rubrene patchessuch as nanoislands-can be effective doping system for the MoS 2 layer to improve the transistor characteristics. A previous study also showed how transistor performance could be optimized using organic nanopatches [28].…”
Section: Comparative I-v Characteristics Of the Pristine And Hybrid Mmentioning
confidence: 96%
“…1(d)). This process induced extra free electrons at the conduction band edge of MoS 2 , and thus the activation energy in the MoS 2 channel could be reduced [28]. In previous reports for molybdenum dithiolene complexes with a p-type organic material dopant, the formation of a narrow depletion region in the channel material by charge doping induced a variation in the charge transport properties [29,30].…”
Section: Comparative I-v Characteristics Of the Pristine And Hybrid Mmentioning
confidence: 98%
“…Molecular doping, where additional charge carriers are generated from the employed dopant materials, is one of the easiest ways to change the charge carrier densities14151617. Interface engineering at the organic semiconductor–gate insulator is another efficient method for controlling the charge carrier densities.…”
mentioning
confidence: 99%